PENGARUH PENGGUNAAN MEDIA VIDEO DALAM PENDIDIKAN KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA REMAJA PUTRI DI SMPS IT INSAN KAMIL - Simanjuntak, Herlina; Yusti, Nuraini; Wati, Putri Sorot (Jurnal Delima Harapan, 2025)
Background: Breast cancer is a global health problem with 2.3 million cases recorded in 2020 and a projected increase in 2040. A delayed diagnosis of breast cancer elevates the likelihood of advanced-stage disease, potentially restricting treatment efficacy and reducing survival rates. Consequently, it is essential for women to acquire knowledge on performing Breast Self-Examination (BSE) and to engage in it consistently, as early detection of breast cancer enhances access to optimal treatment modalities. To increase awareness, adolescent girls need to be provided health education with interesting media. Objective: This study is to find out the impact of health education with video media on the improvement of knowledge of BSE in adolescent girls at SMPS IT Insan Kamil North Cikarang in 2024. Method: This type of research is quantitative. The design of this study was quasi-experimental research with one group pre-test and post-test design. The population and sample in this study were adolescent girls in grade VIII at at SMPS IT Insan Kamil North Cikarang 2024. Sampling technique with a total sampling of 84 respondents. Data collection using questionnaires and data analysis using paired sample t-test. Results: The paired sample t-test statistical test study found that there was an effect of health education with video media on increasing knowledge of BSE with a p-value of 0.000 where p <0.05 which means Ha was accepted Conclusion: There is an influence of health education with video media on increasing knowledge of (BSE) in adolescent girls at SMPS IT Insan Kamil North Cikarang ini 2024. Therefore, it is important to educate adolescent girls to increase knowledge breat self examination as early breast cancer detection every month after period.